EFFECT OF BETA-BLOCKERS ON BLOOD PRESSURE, PERIOPERATIVE COMPLICATIONS AND HOSPITAL STAY DURATION IN PATIENTS WITH INTERMEDIATE RISK OF CARDIOVASCULAR COMPLICATIONS AFTER ROUTINE CHOLECYSTECTOMY: AN OPEN COMPARATIVE RANDOMIZED STUDY - O. L. Barbarash; R. V. Repnikova; T. V. Shoforus; O. I. Golofaeva (Рациональная фармакотерапия в кардиологии)
Background. More than 100 million adults are exposed to noncardiac surgical interventions every year worldwide, and cardiovascular complications happen in 500 000 - 900 000 patients.Aim. To evaluate the efficacy and safety of beta-blocker bisoprolol in the perioperative period in hypertensive patients during routine laparoscopic cholecystectomy.Material and Methods. Hypertensive patients (n=123) scheduled for laparoscopic cholecystectomy were examined. Patients were randomized into 2 groups. Patients of group 1 (n=57) received preoperatively bisoprolol, and patients of group 2 (n=66) had a correction of previously received antihypertensive therapy without beta-blockers addition. Patient examination included traditional preoperative tests as well as ambulatory blood pressure monitoring and echocardiography.Results. Heart rate was significantly lower in group 1 at admission (66.1±6.9 min-1) and before surgery (61.3±6.1 min-1) than in group 2 (74,5±8,2 and 73,9±7,0 min-1, respectively, p<0,001 for both periods). The preoperative use of bisoprolol in hypertensive patients reduced the hemodynamic stress manifestations. Heart rate was significantly lower in patients of group 1 during intubation (p<0,001) as well as systolic blood pressure was lower during the carboxiperitoneum (p<0,05) and at the end of surgical procedure (p<0,05) compared with patients of group 2. Perioperative complications were registered in 11 (19.3%) patients of group 1 and 25 (37.9%) patients of group 2.Conclusion. The preoperative (endoscopic cholecystectomy) use of beta-blocker bisoprolol in hypertensive patients reduces hemodynamic manifestations of stress, hospital stay duration and has a good safety profile.